A password-based authentication approach for edge computing architectures - Laid Kenioua; Brahim Lejdel; Sultan Alamri; Qusai Ramadan (Egyptian Informatics Journal, 2024)
Due to its benefits of low delay and fast response, edge computing has become an essential aid to cloud computing technology and has introduced new options for smart applications. By offloading some of the data processing tasks to the network’s edge, edge computing complements cloud computing. Nevertheless, adopting edge computing introduces several security challenges that must be addressed to ensure safety and reliability. One major concern is data privacy, as sensitive information processed at the edge must be protected from unauthorized access and breaches. Implementing strong encryption, secure authentication protocols, and regular software updates are some of the strategies necessary to enhance security in edge computing environments. In this paper, we present a robust and lightweight mutual authentication technique that is perfectly suited to low devices that can benefit from the edge computing paradigm. After the registration phase, the authentication process can be made in two rounds, the edge node and user can easily authenticate each other. Our approach is evaluated with regard to communication and computation costs realizing 982 bits and 5.955 ms respectively. analysis and experiments prove the high performance of the proposed technique.